Clinical Results and Quality of Life After Transcortical Versus Transcallosal Resection of Adult Lateral and Third Ventricle Lesions: Long-Term Outcome - AlSharif, Mustafa; Stroop, Ralf; Scholz, Martin; Buchfelder, Michael; Wiendieck, Kurt; Shiban, Ehab; Sommer, Björn (World Neurosurgery, 2023)
Background: Resection of intraventricular tumors can be achieved using 2 main operative approaches: transcallosal or transcortical. This study aims to describe preoperative and postoperative factors as well as quality of life (QoL) based on long-term results in these patients. Methods: Patients underwent surgery of primary intraventricular lesions between 2007 and 2020 via a transcortical (group A) or transcallosal (group B) route. The main clinical parameters were completeness of resection, overall survival, surgical complications, postoperative neurologic deficits, and seizure rates. QoL was assessed using a modified questionnaire Short-Form 36 inventory. Results: Forty patients (19 women and 21 men) met the inclusion criteria. Group A consisted of 26 patients (12 women and 14 men; median age 45.5 years ± 16.7 standard deviation) and had lower preoperative tumor volume (confounder) compared with group B (7 women and 7 men; age 50.0 ± 17.4 years). Gross total resection was achieved in 65% in group A and 71% in group B. Follow-up was 7.8 ± 3.9 years. New seizures/permanent neurologic deficits occurred in 27%/15% (group A) and 29%/29% (group B) and surgical complications in 23% of patients. Group B had a higher degree of memory impairment (21%) compared with group A (10%). QoL impairment was present in both groups mainly regarding physical role function and mental health index. Conclusions: Keeping in mind the limitations, transcallosal surgery was associated with a higher probability of neurologic deficits and memory impairment in our series. However, it had fewer surgical complications with similar gross total resection and seizure rates.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Functional outcome; Morbidity; Quality of life; Surgical approach; Ventricle tumor

Early Intravenous Magnesium Sulfate and Its Impact on Cerebral Vasospasm as well as Delayed Cerebral Ischemia in Aneurysmal Subarachnoid Hemorrhage: A Retrospective Matched Case-Control Analysis - Feulner, Julian; Weidinger, Cornelia; Dörfler, Arnd; Birkholz, Torsten; Buchfelder, Michael; Sommer, Björn (World Neurosurgery, 2024)
Background: Magnesium sulfate (MgSO4) is a potential neuroprotective agent for patients with aneurysmal subarachnoid hemorrhage (SAH). We analyzed the effect of early application of intraoperative intravenous MgSO4 and compared cerebral vasospasm (CV), delayed cerebral ischemia (DCI), and neurological outcome in 2 patient cohorts. Methods: A retrospective matched-pair analysis from patients at a single center in Germany was performed without (group A) and with (group B) MgSO4 application <24 hours after diagnosis. Pairs were matched according to the known risk factors for DCI and CV (age, Fisher grade, smoking, severity of SAH). Incidence of CV and DCI and neurological outcome using the modified Rankin Scale score 3 and 12 months after SAH were recorded. Results: The inclusion criteria were met by 196 patients. After risk stratification, 48 patients were included in the final analysis (age 54.2 ± 8.1 years; 30 women and 18 men) and were assigned to group A (n = 24) or group B (n = 24). CV occurred less frequently in group B (33%) than in group A (46%). Likewise, DCI was present in 13% in group B compared with 42% in group A. After 12 months, 22 patients in group B had a favorable functional outcome (modified Rankin Scale score 0–3) compared with 15 patients in group A. Conclusions: In this study, the incidence of CV and DCI was lower in patients receiving intravenous MgSO4 within 24 hours after aneurysmal SAH onset. Favorable functional outcome was more likely in the MgSO4 group after 12 months of follow-up.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Aneurysmal subarachnoid hemorrhage; Cerebral vasospasm; Delayed cerebral ischemia; Functional outcome; Magnesium sulfate

Long-Term Clinical and Radiologic Outcome Following Surgical Treatment of Lumbar Spondylodiscitis: A Retrospective Bicenter Study - Sommer, Björn; Babbe-Pekol, Timo; Feulner, Julian; Richter, Richard Heinrich; Buchfelder, Michael; Shiban, Ehab; Sesselmann, Stefan; Forst, Raimund; Wiendieck, Kurt (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background and Study Aims Spinal instrumentation for spondylodiskitis (SD) remains highly controversial. To date, surgical data are limited to relatively small case series with short-term follow-up data. In this study, we wanted to elucidate the biomechanical, surgical, and neurologic long-term outcomes in these patients. Material and Methods A retrospective analysis from two German primary care hospitals over a 9-year period (2005-2014) was performed. The inclusion criteria were (1) pyogenic lumbar SD, (2) minimum follow-up of 1 year, and (3) surgical instrumentation. The clinical and radiologic outcome was assessed before surgery, at discharge, and at a minimum of 12 months of follow-up. Follow-up included physical examination, laboratory results, CT and MRI scans, as well as assessment of quality of life (QoL) using short-form health survey (SF-36) inventory, Oswestry Disability Questionnaire, and visual analog scale (VAS) spine score. Results Complete data were available in 70 patients (49 males and 21 females, with an age range of 67±12.3 years) with a median follow-up of 6.6 ± 4.2 years. Follow-up data were available in 70 patients after 1 year, in 58 patients after 2 years, and in 44 patients after 6 years. Thirty-five patients underwent posterior stabilization and decompression alone and 35 patients were operated on in a two-stage 360-degree interbody fusion with decompression. Pre- and postoperative angles of the affected motion segment were 17.6 ± 10.2 and 16.1 ± 10.7 degrees in patients with posterior instrumentation only and 21.0 ± 10.2 and 18.3 ± 10.5 degrees in patients with combined anterior/posterior fusion. Vertebral body subsidence was seen in 12 and 6 cases following posterior instrumentation and 360-degree instrumentation, respectively. Nonfusion was encountered in 22 and 11 cases following posterior instrumentation and 360-degree instrumentation, respectively. The length of hospital stay was 35.0 ± 24.5 days. Surgery-associated complication rate was 18% (12/70). New neurologic symptoms occurred in 7% (5/70). Revision surgery was performed in 3% (2/70) due to screw misplacement/hardware failure and in 3% (2/70) due to intraspinal hematoma. Although patients reported a highly impaired pain deception and vitality, physical mobility was unaffected and pain disability during daily activities was moderate. Conclusion Surgical treatment of SD with a staged surgical approach (if needed) is safe and provides very good long-term clinical and radiologic outcome.
CRIS-Team Scopus Importer:2022-07-22
Keywords: biomechanics; diagnostics; functional outcome; quality of life; risk factor; spinal infection; surgical approach; vertebral pyogenic osteomyelitis